Isolation, Identification and Cytotoxicity of a New Noroleanane-Type Triterpene Saponin from Salicornia bigelovii Torr. - Fuqin Guan; Qizhi Wang; Ming Wang; Yu Shan; Yu Chen; Min Yin; Youyi Zhao; Xu Feng; Fei Liu; Jianhua Zhang (Molecules, 2015)
Salicornia bigelovii Torr. has been consumed not only as a popular kind of vegetable, but also as a medicinal plant to treat hypertension, cephalalgia, scurvy and cancer. The present study was designed to investigate its chemical components and cytotoxic activity. A new noroleanane-type triterpene saponin, bigelovii C (1), was separated and purified from Salicornia bigelovii Torr., along with four known triterpene saponins 2–5. The structure of bigelovii C was elucidated as 3-O-(6-O-butyl ester)-β-D-glucuropyranosyl-23-aldehyde-30-norolean-12, 20 (29)-dien-28-oic acid-28-O-β-D-glucopyranoside, according to various spectroscopic analysis and chemical characteristics. Besides Compounds 3 and 5, bigelovii C had potent cytotoxicity against three human cancer cell lines, MCF7 (breast cancer), Lovo (colon cancer) and LN229 (glioblastoma), especially MCF7. Bigelovii C inhibited the growth of MCF7 cells in dose- and time-dependent manners. Flow cytometry analysis revealed that the percentage of apoptotic cells significantly increased upon bigelovii C treatment. Rh123 staining assay indicated that bigelovii C reduced the mitochondrial membrane potential. The mechanism of cell death by bigelovii C may be attributed to the downregulation of Bcl-2 and upregulation of Bax, cleaved caspase-9, caspase-7 and PARP. These results suggested that bigelovii C may impart health benefits when consumed and should be regarded as a potential chemopreventative agent for cancer.